Pemberdayaan Desa Binaan Berbasis Budaya Hukum dengan Penerapan (SIMDES) Sistem Informasi Transparansi Dana Desa di Pulau Gadang - Heni Susanti; Heriyanto Heriyanto; Budi Mulianto; Yusramizza Yusramizza; Hendra Gunawan; Detri Karya; Dwi Yusuf Rafli; Dwi Yuda; Kurniadi Kurniadi; Muhammad Syafii; Evi Yanti (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
The implementation of the Village Financial System plays an important role in facilitating financial reporting and being able to create a transparent and accountable management of village fund allocations in order to create a Good Governance system. The problems that occur in Pulau Gadang Village partners that there are unresolved problems in the village, including the lack of Village Official Skill related to Village Law No. 6 of 2014 and Pulau Gadang Village Regulation No. 04 of 2022 concerning Amendments to the Pulau Gadang Village Budget for the 2022 Fiscal Year. Community service is carried out using lecture and presentation methods, as for the solutions provided by the PKM Team to partners, the first activity is to present material related to the Transparency of Village Fund Financial Management Permendagri number 20 of 2018 concerning Village Financial Management Guidelines That Village Financial Management, then the second speaker discusses related to increasing village finances from the tourism sector. PKM activities run smoothly, it is the hope of the PKM Team that in the future Pulau Gadang Village in managing Village finances can run in accordance with Permendagri number 20 of 2018 concerning Village Financial Management Guidelines and from the tourism sector can develop well and take place sustainably.